Does high-intensity resistance training with suppressed remarkable fatigue enhance the effect of plyometrics training that follows immediately? - Nakata, K.; Mizukawa, H.; Mishima, T. (Journal of Australian Strength and Conditioning, 2020)
It is well known that high-intensity resistance training (HRT) enhance the effect of plyometrics training (PT) that performed followed, and this training mode is commonly called complex training (CT). Typical CT includes HRT that performed with expected maximum number of repetitions. It has been suggested that HRT with expected maximum number of repetitions induces significant fatigue, which reduces the effect of immediate PT. However, it has not been clarified whether HRT protocol suppressing marked fatigue enhance the effect of PT that followed immediately. Therefore, in the present study, we verified high-intensity squat training (HSQ) suppressing remarkable fatigue enhance the effect of jump performance.